2015
DOI: 10.1289/ehp.1307327
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Left Ventricular Geometry, and Systolic Function in Children Exposed to Inorganic Arsenic

Abstract: Background:Inorganic arsenic (iAs) is a ubiquitous element present in the groundwater worldwide. Cardiovascular effects related to iAs exposure have been studied extensively in adult populations. Few epidemiological studies have been focused on iAs exposure–related cardiovascular disease in children.Objective:In this study we investigated the association between iAs exposure, blood pressure (BP), and functional and anatomical echocardiographic parameters in children.Methods:A cross-sectional study of 161 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Many prospective studies have confirmed a strong association between BP levels and risk of CVD [ 24 , 25 ]. A number of study reported that the prevalence of hypertension was positively related to As exposure [ 26 31 ]. In a prospective study, maternal urinary arsenic during pregnancy was correlated with BP in children at 4.5 years of age [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many prospective studies have confirmed a strong association between BP levels and risk of CVD [ 24 , 25 ]. A number of study reported that the prevalence of hypertension was positively related to As exposure [ 26 31 ]. In a prospective study, maternal urinary arsenic during pregnancy was correlated with BP in children at 4.5 years of age [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 In children, early life As exposure has been associated with early indicators of cardiovascular risk, including increased blood pressure, as well as carotid intima media thickness (cIMT). 2022 …”
Section: Introductionmentioning
confidence: 99%
“…There are many risks associated with arsenic exposure including genotoxicity and neurotoxicity [Rocha‐Amador et al, ; Tyler and Allan, ; Jasso‐Pineda et al, ]. Exposure to this metalloid also represents a risk for metabolic disorders [Osorio‐Yáñez et al, and ; Mendez et al, ], respiratory damage [Olivas‐Calderón et al, ; Recio‐Vega et al, ] and diabetes [Del Razo et al, ; Drobná et al, ] at exposure levels comparable to those used in the present study. The carcinogenic potential of arsenic should be considered in exposure scenarios.…”
Section: Introductionmentioning
confidence: 99%